Peran multikulturalisme dalam mempertahankan identitas budaya pada film Ngeri-Ngeri Sedap karya Bene Dion - Anggraeni, Rezki Amelia; Suryaningsih, Sukarni; Widyatwati, Ken; Suryadi, M. (Universitas Mulawarman, 2025)
This study explores the role of openness to Batak culture as the majority culture in the film Ngeri-Ngeri Sedap to maintain its cultural identity amid diversity. The openness referred to here is the recognition and acceptance of the existence of minority cultures, in line with the concept of multiculturalism, to minimize the potential for horizontal conflicts that could threaten the survival of cultures. The research method employs a sociology of literature approach, with Ngeri-Ngeri Sedap as the material object of the study. The data analysis technique uses interpretive analysis with the aid of film narrative structure theory from Himawan Pratista and the concept of multiculturalism proposed by Charles Taylor. As this research is qualitative and descriptive, the findings are narrative. The results of the study indicate that multiculturalism, as a bridge for interaction between minority and majority groups, plays a role in maintaining the existence of each cultural identity within a multicultural society, marked by the creation of a dynamic and harmonious social environment.